Globalization and Political Geography - Federico Etro (Center for Economic Studies and ifo Institute (CESifo), 2003)
I study a model of geopolitical organization endogenizing the size of nations, of their public spending and of their degree of openness. The optimal geography may not be a stable equilibrium and the Alesina-Spolaore bias toward too many nations tends to be confirmed. However, multiple equilibria can emerge with globalization backlash associated with large nations and high protectionism and equilibria with smaller countries and high openness which are also Pareto superior. A dynamic version of the model shows stable paths of decreasing size of nations, increasing globalization and (at least initially) increasing public spending. Such a process seems consistent with the historical experience, but it may converge toward a steady state with excessive globalization, too many countries and typically too much government spending.
Keywords: 330